Vitamin D and parathyroid hormone are associated with gait instability and poor balance performance in mid-age to older aged women - Bird, M.; El Haber, N.; Batchelor, F.; Hill, Keith; Wark, J. (Elsevier, 2018)
Context Vitamin D status and parathyroid hormone (PTH) levels influence the risk of accidental falls in older people, but the mechanisms underlying this effect remain unclear. Objective Investigate the relationship between circulating PTH and 25 hydroxyvitamin D (25-OHD) levels and clinical tests of gait stability and balance as physical fall risk factors. We hypothesized that high levels of PTH and low 25-OHD levels would be significantly associated with gait stability and decreased balance performance. Design Observational cohort study. Setting Australian community. Participants 119 healthy, ambulatory female twin adults aged 47–80 years residing in Victoria, Australia. Outc ome measures Serum PTH and 25-OHD levels with clinical tests of gait stability [double support duration (DSD)] and dynamic balance (Step Test). Associations were investigated by regression analysis and by comparing groups divided by tertiles of PTH ( < 3.5, 3.5–4.9, > 4.9 pmol/L) and 25-OHD ( < 53, 53–75, > 75 nmol/L) using analysis of variance. Results Serum PTH was associated positively with DSD, with an increase of 10.6–15.7% when the mid and highest PTH tertiles were compared to the lowest tertile (p < 0.025) when 25-OHD was included in the regression analysis. 25-OHD was significantly associated with DSD (greater by 10.6–11.1% when lowest and mid-tertiles compared with the highest 25-OHD tertile) (p < 0.025) and dynamic balance (better performance by 12.6% in the highest compared with the lowest 25OHD tertile) (p < 0.025). Conclusion These findings reveal an important new relationship between parathyroid hormone and gait stability parameters and add to understanding of the role of 25-OHD in motor control of gait and dynamic balance in community-dwelling women across a wide age span.